The effects of the Tripartite Free Trade Area: Towards a new Economic geography in Southern, Eastern and Northern Africa? - Andrew Mold; Rodgers Mukwaya (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2015)
This study evaluates the economic impact of the proposed COMESA-SADC-EAC Tripartite Free Trade Area (TFTA) on 26 African countries. It uses the global trade analysis project (GTAP) computable general equilibrium (CGE) model and database to measure the static effects of the establishment of the TFTA on industrial production, trade flows and consumption in the tripartite region. The results indicate a significant increase in intra-regional exports as a result of tariff elimination, boosting intra-regional trade by 29 percent. Particularly encouraging is the fact that the sectors benefiting most are manufacturing ones, such as light and heavy manufacturing, and processed food. Concerns have been raised that industrial production in the TFTA would concentrate in the countries with highest productivity levels - namely, Egypt and South Africa. Simulation results suggest that these fears are exaggerated, with little evidence of concentration of industries in the larger countries.
Keywords: F15; F47; 330; tripartite free trade area; EAC; COMESA; SADC